2018
DOI: 10.3390/ijms19061730
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Conjugated Linoleic Acid-Enriched Cheeses Influence the Levels of Circulating n-3 Highly Unsaturated Fatty Acids in Humans

Abstract: n-3 highly unsaturated fatty acids (n-3 HUFA) directly and indirectly regulate lipid metabolism, energy balance and the inflammatory response. We investigated changes to the n-3 HUFA score of healthy adults, induced by different types and amounts of conjugated linoleic acid (CLA)-enriched (ENCH) cheeses consumed for different periods of time, compared to dietary fish oil (FO) pills (500 mg, each containing 100 mg of eicosapentaenoic and docosahexaenoic acids—EPA+DHA) or α-linolenic acid (ALA)-rich linseed oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 71 publications
3
33
0
Order By: Relevance
“…Consequently, it is feasible that the metabolic effect of C9 on fatty acid metabolism (i.e., increased n-3 HUFA score, DHA/EPA ratio, and DHA biosynthesis) may occur via the activation of PPARα in the liver and then exported in the muscle. Similar results were found in humans [66], where the intake of naturally enriched C9 cheese significantly increased plasma DHA and the n-3 HUFA score and PPARα gene expression, which is also involved in DHA biosynthesis [67]. Further experiments will be carried out to evaluate the expression of a subset of down-stream genes by activating PPAR-α and to investigate the modulatory role of PPAR-δ in lipid-induced alteration of mitochondrial β oxidation in skeletal muscle.…”
Section: Discussionsupporting
confidence: 67%
“…Consequently, it is feasible that the metabolic effect of C9 on fatty acid metabolism (i.e., increased n-3 HUFA score, DHA/EPA ratio, and DHA biosynthesis) may occur via the activation of PPARα in the liver and then exported in the muscle. Similar results were found in humans [66], where the intake of naturally enriched C9 cheese significantly increased plasma DHA and the n-3 HUFA score and PPARα gene expression, which is also involved in DHA biosynthesis [67]. Further experiments will be carried out to evaluate the expression of a subset of down-stream genes by activating PPAR-α and to investigate the modulatory role of PPAR-δ in lipid-induced alteration of mitochondrial β oxidation in skeletal muscle.…”
Section: Discussionsupporting
confidence: 67%
“…This study confirms that the CLA naturally found in ruminant fat is able to significantly increase n-3 HUFA score. In fact, previously, we found that the intake of CLA naturally incorporated into 90 grams of enriched cheese for four weeks, or 50 grams for two months, significantly increased plasma DHA in humans, suggesting that amount and duration are key aspects of CLA intake to induce DHA biosynthesis [38]. In that study, we observed that enriched cheese intake increased PPAR-α gene expression, which is responsible for the induction of key enzymes of peroxisomal β-oxidation [19,48], which is involved in DHA biosynthesis [49].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we aimed to evaluate whether the peculiar nutritional effect of CLA in combination with ALA on increasing n-3 HUFA score, found in humans with dietary CLA-enriched cheese [38,39], would also be confirmed with dietary lamb meat fats which were differentially enriched in CLA and ALA compared to vegetable fats in Zucker rats, a rat model of obesity [40].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there is so far no existing work investigating the physiological effects of this distinct family of PUFAs. Because all these fatty acids were detected whenever RMA was supplemented through diet (Piras et al, 2015;Murru et al, 2018), one cannot conclude that RMA is solely responsible for any noticed benefits. 7 Conclusion: defining the n-7 trans fatty acid family, and opening up new research hypotheses For decades, it has been all about natural trans fatty acids vs. industrial ones as regards to the risk of cardiovascular diseases: for all these fatty acids, a negative connotation has remained.…”
Section: Rumenic Acid (Rma)mentioning
confidence: 99%